Post Caesarean Vesicouterine Fistula Causing Menouria - Sultana, R; Haque, N (Medicine Today, 2013)
Vesicouterine fistula is an uncommon urogenital fistula. The incidence is on the rise because of increasing incidence of Caesarean sections. Cyclical Haematuria or Menouria is an important clinical feature of this fistula which may or may not be associated with urinary incontinence depending on the location of the fistulous tract. We present a case report of Post caesarean section Vesicouterine fistula following 2 Caesarean sections. This was successfully managed by laparotomy with repair of fistulous tract in bladder wall and Total Abdominal Hysterectomy for multiple Fibroid uterus done. Menouria is a rare event in Gynecology and one should always keep this possibility in mind when there is cyclical haematuria. A 42 year old Bangladeshi woman was hospitalized with complaints of menorrhagia, lower abdominal pain for last 8 years, cyclical hematuria for last 20 years. She was mildly anemic, haemodynamically stable and regularly menstruating women. The primary Ultrasound scans suggested multiple fibroid with cystic ovary in left side. Cystoscopy was done and findings are a fistulous opening in the bladder measuring around 7mm in size. It was supratrigonal in position. The patient had no history of Endometriosis, Pelvic irradiation therapy, Inflammatory disease, Trauma or Malignancy. Initially there was dilemma in her diagnosis and the patient was diagnosed as a case of bladder Endometriosis besides fibroid uterus. So surgery was planned and Total Abdominal Hysterectomy & bilateral salphingo-oophorectomy done. There was a fistula about 3cm × 2cm in the lower part of the body of uterus connecting with the base of Bladder. Fistula repaired after dissection, patient follow up done and catheter removed after 14 days without any complications. Vesicouterine fistula can be prevented if care is taken to separate the bladder from the uterus during repeat Caesarean sections. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.16072 Medicine Today 2013 Vol.25(1): 46-48